Transmission of Environmental Knowledge and Land Skills in Adaptation to Climate Change in the Arctic - Pearce, Tristan (University of Guelph, 2011)
This thesis investigates the relationships between skills transmission and human adaptation to climate change. Elements of the relationships are empirically examined in an arctic community to document how environmental knowledge and land skills (referred to hereafter together as ‘land skills’) are transmitted among Inuit men and what role, if any, skills transmission plays in adaptation to climate change with respect to subsistence harvesting. It is well documented that climate change is already being experienced in the Arctic with implications for Inuit subsistence harvesting. The ability of Inuit to adapt to changing environmental conditions in the past has been associated with a profound knowledge of the Arctic ecosphere and land skills, which were transmitted from the older generations to the younger through hands-on training in the environment. Based on a review of vulnerability and skills transmission scholarship, a conceptual model for interpreting the relationships between skills transmission and adaptive capacity is developed. The model conceptualizes land skills as a key determinant of Inuit adaptive capacity to deal with climatic changes that affect subsistence. The ability of a hunter to draw on land skills to adapt to changing conditions also depends on whether or not a given skill has been transmitted, and transmission success depends on the level of skill mastery. The transmission of land skills was studied among Inuit men in Ulukhaktok, Northwest Territories, Canada. The research found that there is a difference in the rate of land skills transmission among generations, with average transmission rates lowest among younger respondents. Several skills had not been transmitted, or were transmitted incompletely among younger respondents. Whereas these same skills had been transmitted by that age among older Inuit. Changes in skills transmission are attributable to changes in the educational environment, loss of native language, absence of skills teachers, and declining levels of involvement in some ...